Effectiveness and cytotoxicity of two desensitizing agents: a dentin permeability measurement and dentin barrier testing in vitro study - Ruodan Jiang; Yongxiang Xu; Feilong Wang; Hong Lin (BMC, 2022)
Abstract Background When evaluating the efficacy and safety of various desensitizing products in vitro, their mechanism of action and clinical utility should be considered during test model selection. This study aimed to evaluate the effects of two desensitizers, an in-office use material and an at-home use material, on dentin specimen permeability, and their dentin barrier cytotoxicity with appropriate test models. Methods Two materials, GLUMA desensitizer (GLU) containing glutaraldehyde and remineralizing and desensitizing gel (RD) containing sodium fluoride and fumed silica, were selected. Human dentin specimens were divided into three groups (n = 6): in groups 1 and 2, GLU was applied, and in group 3, RD was applied and immersed in artificial saliva (AS) for 24 h. Dentin specimen permeability before and after each treatment/post-treatment was measured using a hydraulic device under a pressure of 20 cm H2O. The perfusion fluid was deionized water, except in group 2 where 2% bovine serum albumin (BSA) was used. The representative specimens before and after treatment from each group were investigated using scanning electron microscopy. To measure cytotoxicity, test materials were applied to the occlusal surfaces of human dentin disks under which three-dimensional cell scaffolds were placed. After 24-h contact within the test device, cell viability was measured via 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assays. Results GLU significantly reduced the dentin permeability and occluded the dentinal tubules when 2% BSA was used as perfusion fluid. RD significantly reduced dentin permeability and occluded the tubules, but permeability rebounded after AS immersion. GLU significantly decreased cell viability, but RD was non-cytotoxic. Conclusions In vitro GLU application induced effective dentinal tubule occlusion only following the introduction of simulated dentinal fluid. RD provided effective tubule occlusion, but its full remineralization potential was not realized after a short period of immersion in AS. GLU may harm the pulp, whereas RD is sufficiently biocompatible.